Pengaruh Lama dan Suhu Pengeringan Terhadap Karakteristik Fisikokimia Tepung Beras Merah (Oryza nivara): Pengaruh Lama dan Suhu Pengeringan Terhadap Karakteristik Fisikokimia Tepung Beras Merah (Oryza nivara) - Merynda Indriyani Syafutri; Friska Syaiful; Eka Lidiasari; Dela Pusvita (Universitas Bangka Belitung, 2020)
Red rice is known to have advantages, i.e. contain fiber and anthocyanin that have functional properties. The potential of red rice needs to be explored more intensively through various studies. One effort to develop brown rice as food is to process it into flour. In the process of flour processing, there are several steps that must be considered to get flour with good physicochemical properties, such as drying and grinding. The purpose of this research was to learn the effect of drying time and temperature on the physicochemical characteristics of red rice flour. Randomized Block Design factorial was used in this research. The treatment factors were drying time (A) and drying temperature (B). Factor A consisted of three levels i.e. 1 hour, 2 hours, and 3 hours, and factor B also consisted of three levels i.e. 50°C, 55°C, and 60°C. The parameters observed in this study were yield, bulk density, water holding capacity, swelling power, solubility, moisture content, and amylose content of red rice flour. The results showed that the drying times and temperatures significantly reduced yield, bulk density, and moisture content, but significantly increased water holding capacity, swelling power, solubility, and amylose content of red rice flour. The moisture content of red rice flour was in accordance with the standards (SNI 3549; 2009).